The role of fibrinogen-like protein 1 in immune escape and tumor growth mechanism of Warthin's tumor - Arifin, Grandissyaikhu Kamila; Indriana, Tecky; Kosasih, Jane; Dharmayanti, Agustin Wulan Suci; Syafriadi, Mei (Dental Journal (Majalah Kedokteran Gigi), 2024)
Background: One of the benign tumors of the salivary glands is Warthin's Tumor (WT), which consists of cystic bilayer papillary epithelial cells accompanied by the presence of a lymphoid stroma. Several cases have been reported to turn malignant. One of the markers developed to identify tumor proteins is fibrinogen-like protein 1 (FGL1). Along with lymphocyte-activation gene 3 (LAG-3), FGL1 establishes an immune checkpoint pathway that plays a role in the mechanism of tumor immune escape. Not much has been reported regarding FGL1 expression in WT, but some studies have reported that its expression is associated with tumor growth. Purpose: This study aims to analyze the location of FGL1 expression in WT and its relation to the mechanism of tumor immune release through the interaction between FGL1 and LAG-3. Methods: Cases of WT (n = 11) and breast cancer (n = 1) were used as positive controls. All cases were stained with hematoxylin-eosin and Recombinant Anti-FGL1 antibody. The FGL1 expression was observed in the cell membrane, cytoplasm, and lymphoid stroma. The results are presented in the form of figures. Results: All cases of WT expressed FGL1 in the cell membrane, cytoplasm, and lymphoid stroma. Its expression in the cell membrane and cytoplasm is possibly related to the process of tumorigenesis and the increasing size of the lesion. Additionally, its expression is seen in the lymphoid stroma, which is closely related to immune escape by inhibiting lymphocytes against tumor cells. Conclusion: Warthin's tumor cells express FGL1, and this expression plays a role in tumor immune escape mechanisms and tumor growth.